Comparative Advantage, Relative Wages, and the Accumulation of Human Capital - Coen N. Teulings (Tinbergen Institute, 2002)
I apply Ricardo's principle of comparative advantage to a theory of factor substitutability in a model with a continuum of worker and job types. Highly skilled workers have a comparative advantage in complex jobs. The model satisfies the distance-dependent elasticity of substitution (DIDES) characteristic: substitutability between types declines with their skill distance. I analyze changes in relative wages due to human capital accumulation. The concept of a complexity dispersion parameter or compression elasticity is introduced. Empirical studies suggest its value to be equal to two: a 1 percent increase in the stock of human capital reduces the Mincerian return by 2 percent.
Keywords: D30; J24; 330; assignment; wage distribution; human capital.; Humankapital; Faktorsubstitution; Komparativer Vorteil; Hochqualifizierte Arbeitskräfte; Lohnstruktur; Bildungsinvestition; Theorie